Recovered Cities. - Miszewska, Barbara (Bulletin of Geography. Socio-economic Series, 2007)
There is a large group of cities in Poland, which lost and re-gained their urban status. Many of those cities lost their urban status as the result of administrative reforms introduced by partitioning states in the 19th century, and after WWII. Restoration of their urban status took place after WWI and/or WWII. In the majority of the cities, the population did not exceed 10,000 inhabitants. Their contribution to overall urbanization of the country was rather limited.